Journal Club: a group of research experience - Patricia Bover Draganov; Maria Regina Guimarães Silva; Vanessa Ribeiro Neves; Maria Cristina Sanna
ABSTRACT Introduction: the Journal Club (JC) is a teaching and learning strategy developed by individuals who meet to discuss scientific articles in periodicals. Objective: to describe the experience of the JC strategy at the Group for Studies and Research in Health Services Administration and Nursing Management (Gepag). Method: case studies or scientific research demonstration mode of practical experience for the understanding and justification of facts. Results: Gepag JC emerged in 2008 and, in 2014, was computerized with the Google Drive®, in order to increase its scope and optimize the Group›s meetings. From April to May 2014, the instrument was tested and adjusted, resulting in advancements. Final considerations: the advantages involved optimizing the time of meetings, facilitation of access to publications of interest to the Group and creating the database to support future research.